Facilities management outsourcing: theoretical trends and evidence from practice in Nigeria and United Kingdom - Ikediashi, Dubem I.; Odesola, Isaac A. (International Journal of Strategic Property Management, 2016)
Previous research has acknowledged facilities management (FM) as a discipline that optimises the delivery of facilities and its related services through use of high profile strategies that provide cost effective, high quality and integrated approach to the concept of managing facilities and its related services. The purpose of this paper is to examine the theoretical trends in outsourcing of FM functions and the current state of FM practice using Nigeria and UK as case studies. This re- search used a combination of literature review and questionnaire survey. The questionnaire survey was conducted to further explore (through comparative analysis) the perception of 30 (15 from UK and 15 from Nigeria) carefully selected facilities managers in UK and Nigeria who are subscribing members of British Institute of Facilities Management (BIFM) and International Facilities Manage- ment Association (IFMA) Nigeria’s chapter respectively. 22 respondents consisting of 13 received from UK respondents and 9 from Nigeria responded to the survey giving a response rate of 73%. Findings reveal among others that FM has grown from the traditional day-to-day operational management to being a strategic management tool; while janitorial services and facilities maintenance remain the most outsourced FM services.